Literatur Review: Hubungan Dukungan Keluarga dengan Tingkat Depresi Lansia di Kelurahan Pejuang Kota Bekasi - Nasywa Oktavia Melani; Nadia Oktiffany Putri (Journal of Educational Innovation and Public Health, 2026)
This study aims to examine the relationship between family support and depression levels among the elderly in Pejuang Village, Bekasi City, through a descriptive-narrative literature review. The review analyzed relevant scientific articles discussing family support, social support, and depression in older adults. Literature was selected based on the suitability of the elderly population, the presence of family or social support variables, and the measurement of depressive symptoms or depression levels. The analysis compared each article’s objectives, research design, respondent characteristics, instruments, findings, and conclusions. The results indicate that most studies found a relationship between family support or social support and depression among the elderly. Adequate family support, including emotional, instrumental, informational, and appraisal support, helps older adults feel cared for, valued, secure, and better able to adapt to the aging process. Preliminary findings at the Elderly Posyandu in Pejuang Village also show variations in family support and depression levels among elderly participants. Conversely, limited family support may increase loneliness, psychological distress, and depressive symptoms. Therefore, family support functions as a protective factor in reducing depression risk among older adults. Strengthening the involvement of families, health workers, and elderly posyandu cadres is necessary as a promotive and preventive strategy to maintain psychological well-being through education, early detection, and sustainable community-based assistance for vulnerable elderly groups living in community and family environments.